New Product Launch Proficiency and Performance in MSMEs: Mediation Effects of Product Innovation - Hendri Herman; Tri Yuwono; Yuli Astini; Sigit Ary Wijayanto; Altug Ocak (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: The creative industries (culinary, fashion, and crafts) are growing rapidly and have become a magnet for investment and a pillar of Central Java's economy. Many Micro, Small, and Medium Enterprises (MSMEs) in the culinary, fashion, and crafts sectors generate creative ideas. However, they are still constrained by a lack of systematic launch capabilities, such as market testing, tactical planning, and budget management for new product launches, which often lead to innovation failures. Therefore, it is important to analyze how New Product Launch Proficiency can improve the performance of culinary, fashion, and craft MSMEs, which have great potential as a new center of economic growth.Purpose: This study investigates the relationship between New Product Launch Proficiency (NPLP) and New Product Performance (NPP) mediated by Product Innovation (PI). Design/methodology/approach: This quantitative study uses data from 284 MSMEs in the creative industries (fashion, culinary, and crafts) from 15 districts in Central Java, Indonesia. The data were analyzed using Partial Least Squares-Structural Equation Modelling (PLS-SEM). This study used indicators of new product launch proficiency, such in market testing competence, tactical planning knowledge, and budget expertise for launch. Indicators of new product performance include new product portfolio, development success, sales performance, and customer acceptance. Indicators of product innovation include product improvement, product diversification, and market penetration.Findings/Result: The results show that new product launch proficiency has a positive impact on product innovation and new product performance. Product innovation was also found to mediate the relationship between new product launch proficiency and new product performance. Conclusion: This research can be a reference for MSMEs and policymakers to adopt new product launch proficiency through product innovation as an important strategy for the growth of MSMEs. MSMEs should adopt simple routines for market testing, tactical launch plans, cross-functional teams, shared supplier networks, and low-cost digital tools to expand new product proficiency.Originality/value (State of the art): This study provides a new perspective on how Creative Industry MSMEs in developing countries especially in Central Java, Indonesia to develop new product launch proficiency and product innovation, which will increase their competitive advantage and achieve sustainable growth. Keywords: msme, nplp, new product performance, launch proficiency, product innovation